Meeting the infrastructure challenge in Latin America and the Caribbean. (Washington, D.C. World Bank, 1995)
Annotation The steady deterioration of infrastructure in Latin America and the Caribbean has significantly reduced the region's competitiveness in the global market. Inefficient public sector monopolies are widely blamed for the failure of infrastruc ture to provide adequate services. The study looks at the historical parallels between improvements in infrastructure and economic growth in this region. It examines the causes of the decline in infrastructure and presents options for reform. In recommending that reforms be systematic and pervasive, the study proposes that World Bank assistance should raise operating and investment efficiency in the power, telecommunications, transport, and water and sanitation sectors. The report also urges governments to create a regulatory framework. Also available in Spanish: (ISBN 0-8213-3029-2) Stock No. 13029.
Electronic reproduction.
Keywords: Infrastructure (Economics) -- Caribbean Area; Infrastructure (Economics) -- Latin America; Electronic books